Teenagers lifestyles : screen time and physical activity - Pombeiro, Miguel Fialho (2015)
This study aims to characterize the lifestyle (LS) of private school Portuguese students. Five lifestyle profiles (LSP) were recognized and interpreted based on physical activity (PA) and screen time (ST). The methodology and tools used in this study are the result of an adaptation of the international study Health Behaviour in School-aged Children conducted under the auspices of the World Health Organization. The participants were an extension of the Portuguese sample integrated in that study, recruiting students from private schools in Lisbon (Portugal). The study included 1385 students of both genders, with an average of 13.6 years of age (SD=1.84). The results showed that in private schools, strategies to promote healthy LSP should consider the students specific profile identified by the practice of PA and ST. The increasing of technological development, driven by policies encouraging the acquisition of technological means, conducted these students to reduce the practice of PA. They should therefore be accompanied by strategies to promote PA practice and screen time consumption education.